Sistem Informasi Promosi Berbasis Web Pada UMKM Jajanan Aulia - Ternando , Dayu; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2022)
At this time in an era where to disseminate or search for information using internet media without any limitations, the current rapid business competition requires business people to always follow market developments and the wishes of the market. UMKM Jajanan Aulia are experiencing limited time constraints in promoting their products, so the marketing activities carried out by UMKM Jajanan Aulia are currently not being managed properly. Therefore, the main problem faced is marketing, especially in the field of promotion. The purpose of this research: object-oriented approach using UML (unified modeling language). This research produces a prototype web-based promotional system design that uses the programming language PHP (Hypertext Preprocessor) and database MySQL (My Structured Query Language), it is hoped that this information system prototype is developed so that it can actually be applied to UMKM Jajanan Aulia to support all business processes from a website-based promotional information system.